Analisa Pengendalian Kualitas Produk Pipa Besi pada CV. XYZ dengan Metode Statistical Quality Control (SQC) - Huda, Fauzi Lukman; Muhimatul Khoiroh, Siti (Fakultas Teknik UMRI, 2025)
This research investigates the quality control system for iron pipe products at CV. XYZ through the application of Statistical Quality Control (SQC). Recognizing the critical role of quality control in ensuring product standards and customer satisfaction within manufacturing, the study employs SQC methodologies, including control charts, Pareto diagrams, and fishbone diagrams, to analyze production process variations. Production data on iron pipe defects over a specific period November 2024 to May 2025. The analysis revealed prevalent defect types and indicated a statistically uncontrolled production process. Consequently, the study recommends a thorough evaluation and improvement of the underlying processes contributing to quality issues. Consistent implementation of SQC is projected to enable CV. XYZ to enhance product quality, minimize defects, and improve overall production efficiency.